Case Report on Bilateral Retinoblastoma in Older Children - Chetan Saoji; Sonal Muley; Ekanksha Kanfade; Sachin Daigavhane (Indian Journal of Forensic Medicine & Toxicology, 2021)
Retinoblastoma is a rare intraocular malignant tumour more commonly seen in children below five years of age. We presented a rare case of retinoblastoma in a 7 year old child who came to the ophthalmology OPD with complaints of loss of vision in both eye and deviation in right eye. Fundus examination showed multiple floating cotton ball opacities in vitreous cavity. B-scan was suggestive of Group E retinoblastoma in right eye and Group D retinoblastoma in left eye. To conclude, any unexplained visual loss in children of any age should be examined extensively by an ophthalmologist, as the risk of retinoblastoma cannot be ruled out.